Nilai Moral Dalam Novel Ning Anak Wayang Karya Niken dan Anjar Kajian: Sosiologi Sastra - Fitri Auliani; Rosliana Lubis; Emma Marsella (Asosiasi Dosen Muda Indonesia, 2025)
This research is motivated by the importance of moral values in everyday life. Moral values aim to shape human character or morals into a good person. This study aims to describe the moral values contained in the novel Ning Anak Wayang by Niken and Anjar study: Sociology of Literature. This study uses a qualitative descriptive method. The results of this study indicate that researchers use the theory according to Wicaksono (2014: 276-281) which states that moral values consist of several sub-values, namely: the relationship between humans and their God, the relationship between humans and themselves, and the relationship between humans and other humans in the social sphere.